Analisis Kesalahan Berbahasa Indonesia Pada Papan Nama Toko Dan Reklame Di Jalan Jenderal Sudirman Palembang - Rayan Rayan; Ratu Wardarita (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
The choice of words and forms of advertisements on billboards or name boards is intended to be  able to attract people's attention. Billboards or signboard makers make it creatively. However, the use of the advertisement language tends to make mistakes. This study aims to describe the errors in Indonesian on billboards and name boards on Jalan Jenderal Sudirman Palembang. Qualitative descriptive research method with data sources in the form of 27 shop signboards and 3 billboards. The data analysis technique used the intralingual matching method. The results of the study concluded: 1) language writing errors on shop signboards are categorized into logical syntax of sentences, writing of abbreviations, use of punctuation marks, writing foreign languages, conjunctions, writing numeric units, composition of phrases, and foreign language structure (MD) and 2) language writing errors on billboards are categorized as using foreign languages and writing websites. Such mistakes are in writing the words Jl. ”,“No”,“Fa.”, “PT.”, And “PD.”, Which should be written as“ Jln ”, “No.”, “Fa”, “PT” , and "PD".